Analisis Antioksidan dan Mutu Organoleptik Snack Bar dari Kacang Gude dan Ubi Jalar Kuning: Antioxidant Analysis and Organoleptic Quality of Snack Bars From Pigeon Pea and Yellow Sweet Potato - Husnul Khotimah; Lingga Gita Dwikasari; Eko Basuki; Siska Cicilia; Riezka Zuhriatika Rasyda; Satrijo Saloko; Dody Handito; Setyaning Pawestri (Jurnal Teknologi dan Mutu Pangan, 2026)
Snack bars were an easy‑to‑consume foods shaped like bars. Snack bars that circulated in the market at that time largely used imported raw materials and highlighted their value as sources of carbohydrates, protein, and fiber. But, snack bars as antioxidant sources had not existed up to that point. Local ingredients such as pigeon pea and sweet potato were used as alternative substitutes for imported ingredients due to their high antioxidant potential. This study aimed to determine the rasio effect of pigeon pea and sweet potato on the antioxidant activity and organoleptics of snack bars. The parameters tested were antioxidant activity, total phenolic content, and organoleptics (color, aroma, texture, and taste), assessed using scoring and hedonic methods. The results showed the best treatment  was the snack bar with 60% pigeon pea and 40% sweet potato ratio, which resulted 78.225% antioxidant activity, 11.063 total phenol content, a balanced distribution of black and yellow colors, a slightly beany aroma, a slightly crunchy texture, and a neutral taste.